PENGARUH PERBANDINGAN ECENG GONDOK DAN KOTORAN SAPI TERHADAP PROSES FERMENTASI UNTUK MENDAPATKAN ENERGI BIOGAS - Kms Ridhuan (JURNAL MECHANICAL, 2012)
levels and low lignin content of potential to be used as raw material for production of biogas. As well biodegradatif Cow manure contains bacteria that can initiate and sustain the production of biogas and water can accelerate the growth of microorganisms and methane-producing organisms are more optimum.This study aims to examine the ratio of water hyacinth, cow dung and water to biogas production better. Water hyacinth and leaves cut approximately 2 to 3 cm, cow dung and water and put into a plastic into Kriya reactor with a capacity of 120 liters and with airtight closed anaerobic process with two different ratio 10:9:48 (kg) and 11:14 : 42 (kg) with a time of 70 days. Parameters measured pressure, volume and temperature of biogas.The results of the study showed that the optimum ratio between the water hyacinth, cow dung and water is 11:14:42 (kg) with the highest volume of 12 492 liters and the highest pressure 109.3 kN/m2, as well as high-pressure hourly te 4100 N/m2. The difference is clearly visible, especially in the pressure measurement, the ratio of 11:14:42 (kg) is even better. The ideal fermentation time in both comparisons are even up to 60 days to 70 days biogas production but there is still very little or small. With time optimum biogas production is starting on day 7 to day 20.Keywords: Biogas, water hyacinth, cow manure